DEVELOPMENT OF GUIDED TRAINING MODEL BASED ON PROBLEM BASED LEARNING FOR STATE JUNIOR HIGH SCHOOL TEACHERS 4 MINAS SIAK DISTRICT RIAU PROVINCE - Sumanti, Titik; Minawati, Rosta; Mulyadi (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to address the challenges in developing a Problem-Based Learning (PBL)-based guided training model for teachers at SMP Negeri 4 Minas, Siak District. The challenges include teachers' limited understanding of PBL concepts and applications, resistance to changing teaching paradigms, and the lack of effective evaluation methods for optimizing PBL implementation. Methods: The research employed a qualitative approach with fieldwork as its methodology. Data were collected from both primary and secondary sources. Primary data were obtained directly from teachers and students, while secondary data were gathered from school documentation. Results: The research findings indicate that the guided training process positively impacted the teachers' competencies in implementing the PBL model. Teachers transitioned from predominantly lecture-based methods to becoming more interactive facilitators, enhancing student engagement. The application of PBL in classrooms improved students' critical thinking, collaboration, and problem-solving skills. These improvements contributed to better student learning outcomes and an overall increase in the quality of education. Novelty: This study highlights the effectiveness of guided training in transforming teaching practices and improving educational quality through the PBL approach. It provides a practical framework for developing teacher competencies, addressing paradigm shifts in teaching methodologies, and optimizing evaluation processes to enhance the application of innovative learning models in schools.